Personality Disorder and Physical Health Comorbidities: A Link With Bone Health? - Williams, Lana J.; Quirk, Shae E.; Koivumaa-Honkanen, Heli; Honkanen, Risto; Pasco, Julie A.; Stuart, Amanda L.; Kavanagh, Bianca E.; Heikkinen, Jeremi; Berk, Michael (Frontiers in Psychiatry, 2020)
We examined whether personality disorder (any, Clusters A/B/C) were associated with bone mineral density (BMD) in a population-based sample of Australian women (n=696). Personality and mood disorders were assessed using semi-structured diagnostic interviews. BMD was measured at the spine, hip and total body using dual energy x-ray absorptiometry (GE-Lunar Prodigy). Anthropometrics, medication use, physical conditions, and lifestyle factors were documented. The association between personality disorder (any, Cluster A/B/C) and BMD (spine/hip/total body) was examined with multiple linear regression models. The best models were identified by backwards elimination including age, weight, physical activity, smoking status, alcohol consumption, dietary calcium intake, mood disorders, physical multimorbidity, socioeconomic status, and medications affecting bone. The variables were retained in the model if p<0.05. All potential interactions in final models were tested. Those with Cluster A personality disorder, compared to those without, had 6.7% lower hip BMD (age, weight adjusted mean 0.853 [95%CI 0.803-0.903] vs 0.910 [95%CI 0.901-0.919] g/cm2, p=0.027) and 3.4% lower total body BMD (age, weight, smoking, alcohol, calcium adjusted mean 1.102 [95%CI 1.064-1.140] vs 1.139 [95%CI 1.128-1.150] g/cm2, p=0.056). No associations were observed between Cluster B/C personality disorders and hip/total body BMD or between any of the personality disorder Clusters and spine BMD. To our knowledge, this study is the first to investigate bone health of women with personality disorder in a population-based sample. Given the paucity of literature, replication, and longitudinal research including the examination of underlying mechanisms and sex differences is warranted.